PENERAPAN KONSEP PARALLEL DALAM STRUKTUR 3 BABAK PADA PENULISAN SKRIP FILM FIKSI DRAMA FANTASI “LOKA GAMA” - Prayudi, Kadek Denika Indra; Putra, Ida Bagus Hari Kayana; Prabhawita, Gede Basuyoga (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
This script raises the theme of family love, telling the story of a daughter's struggle who crosses a parallel world to save her father from chronic heart disease. The parallel world is depicted through the Tri Loka teachings in Hinduism which consist of Bhur Loka, Bwah Loka, and Swah Loka. The creative process begins with exploring ideas, selecting themes, and developing a storyline that is aligned with a three-act structure. In writing, the author pays attention to narrative elements such as characterization, dialogue, and the use of traditional lontar media as symbolic and aesthetic elements. The film is designed with a strong narrative style to create an emotional and culturally relevant story.